Β-Arrestin1 promotes the self-renewal of the leukemia-initiating cell-enriched subpopulation in B-lineage acute lymphoblastic leukemia related to DNMT1 activity. Issue 1 (1st February 2015) - Shu, Yi; Zhou, Xiaoyan; Qi, Xinkun; Liu, Shan; Li, Kang; Tan, Junjie; Liu, Zhidai; Yu, Jie; Zhang, Penghui; Zou, Lin
Hightlights β-Arrestin1 is elevated in LICs from B-ALL. β-Arrestin1 enhances the self-renewal of LICs from B-ALL. The activity of DNMT1 is essential for the self-renewal of LICs from B-ALL. β-Arrestin1 promotes the activity of DNMT1, thus reduces the expression of PTEN in LICs from B-ALL.